Stress and glucocorticoid modulation of feeding and metabolism - Balsevich, G. (Neurobiol Stress, 2019)
This perspective highlights research presented as part of the symposium entitled, “Stress and Glucocorticoid Modulation of Feeding and Metabolism” at the 2018 Neurobiology of Stress Workshop held in Banff, AB, Canada. The symposium comprised five researchers at different career stages who each study different aspects of the interaction between the stress response and metabolic control. Their collective results reveal the complexity of this relationship in terms of behavioural and physiological outcomes. Their work emphasizes the need to consider the level of interaction (cellular, tissue, systems) as well as the timing and context in which the interaction is studied. Rather than a comprehensive review on the work presented at the Symposium, here we discuss recurring themes that emerged at the biennial workshop, which address new avenues of research that will drive the field forward.